The Recipient of the Bronze Bowl from Kınık - Simon, Zsolt (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2018)
Taprammi, a high-ranking Hittite dignitary, is known from many sources (see the analysis of Peled 2013: 790-794 with refs.). One of them is a bronze bowl decorated with hunting scenes, found in the neighbourhood of Kınık in Northern Anatolia (published in Emre – Çınaroğlu 1993: 864-701, the bowl and its inscriptions are also known as ‘Kastamonu’). The bowl shows a dedicatory inscription of Taprammi, the meaning of which is basically clear (Hawkins 1993, here in updated transliteration, and without translating the problematic phrase BONUS2.VIR2 [a title? a blessing?, see the critical discussion in Massi 2009 with refs.]): zi/a CAELUM.PI (or SCUTRA) DEUS.SCRIBA BONUS2.VIR2 EUNUCHUS2 LEPUS+ra/i-mi BONUS2.VIR2 EUNUCHUS2 PONERE ‘Taprammi, the eunuch placed this bowl to DEUS.SCRIBA.’